Da aplicabilidade do negócio jurídico processual na recuperação judicial de empresas - Domingos, Carlos Eduardo Quadros (2018)
The present study has the scope of analyzing the applicability of the legal business process in the scope of business reorganization, contemplated by Law 11,101 of February 9, 2005. The structure of this scientific work will be based on the following exams: (i) legal business in the sphere of civil law, encompassing in this item also the theory of legal fact; (ii) the legal business process, provided for in Articles 190 and 191 of the Code of Civil Procedure of 2015, demonstrating the limits of content, form of concretization and hypothesis of invalidation; (iii) business reorganization based on their procedure, purpose, legal nature and applicable legal principles; and (iv) the compatibility of the legal business process in the business reorganization, addressing concrete situations of celebration